Maternal health - Mohd Arifin, Siti Roshaidai (IIUM Press, International Islamic University Malaysia, 2018)
Chapter 1- Postnatal depression (PND) is a common maternal mental health problem develops in women after childbirth. Sociodemographic, social support and cultural practices may all contribute to postnatal mood and ability to cope with maternal responsibilities. The objective of this study was to determine the association between postnatal depression and sociocultural practices among postnatal mothers. The self-administered questionnaires were distributed to 260 postnatal mothers attending Maternal and Health (MCH) Clinics in Kuantan. Data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and items assessing sociodemographics, social support and cultural practices. Statistical analysis of the data was carried out using SPSS version 20.0. Descriptive data was used to analyze sociodemographic data, social support and cultural practices. Chi square test was used to test the association between sociodemographic data and PND, while independent T- test was used to test continuous data of cultural practices with PND. The prevalence of PND was 15.4%. There was no significant difference between sociodemographic and PND. There was no significant difference between social support and PND. There was no association between cultural practices and PND.